The National Council of Canadian Labour - Thomas, Clive (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1957)
SummaryThe position of the National Council of Canadian Labour towards the Canadian Congress is that the CLC is simply the newest and the most spectacular "front" for international (American) unionism created in Canada. The author explains briefly in this article the reasons for such a statement.